Hemipelvectomy by chondrosarcoma. - Domínguez, Carlos; Iraola, María L; Delgado, Bolívar (Cirugía del Uruguay, 1985)
A palien! treated by hemipelvectomy for a pelvic chondrosarcoma is presented. The comments and conclusions are mentioned with the experience of the literature consulted.